How May Coexisting Frailty Influence Adherence to Treatment in Elderly Hypertensive Patients? - Bartosz Uchmanowicz; Anna Chudiak; Izabella Uchmanowicz; Grzegorz Mazur (International Journal of Hypertension)
Background. Hypertension is considered to be the most common condition in the general population. It is the most important risk factor for premature deaths in the world. Treatment compliance at every stage is a condition for successful antihypertensive therapy, and improving the effectiveness of treatment is a major goal in preventing cardiovascular incidents. Treatment noncompliance and lack of cooperation stem from numerous problems of older age, including frailty syndrome. Objective. To evaluate the effect of frailty syndrome on treatment compliance in older patients with hypertension. Methods. The study sample consisted of 160 patients (91 women, 69 men) with hypertension aged 65 to 78 (mean = 72.09, SD = 7.98 years), hospitalized at the University Clinical Hospital due to exacerbation of disease symptoms. Standardised research tools were used: the Tilburg Frailty Indicator questionnaire and the questionnaire for the assessment of treatment compliance in patients with hypertension, the Hill-Bone Compliance to High Blood Pressure Therapy Scale. Results. Frailty syndrome was diagnosed in 65.62% of patients: 35.62% with mild, 29.38% with moderate, and 0.62% with severe frailty. The treatment compliance was 36.14%. The prevalence of the FS and its three components (physical, psychological, social) significantly affected (p <0.05) the global score of the Hill-Bone Compliance to High Blood Pressure Therapy Scale and all subscales: “reduced sodium intake”, “appointment keeping”, and “antihypertensive medication taking”. Conclusions. The coexistence of frailty syndrome has a negative impact on the compliance of older patients with hypertension. Diagnosis of frailty and of the associated difficulties in adhering to treatment may allow for targeting the older patients with a poorer prognosis and at risk of complications from untreated or undertreated hypertension and for planning interventions to improve hypertension control.